Global patterns of marine megafauna functional diversity - ARIANNA CHITI (2022)
Marine megafauna (i.e. large-bodied marine animals with a body mass of >45 kg) perform important ecological roles in the oceans, yet their contributions to the stability and resilience of ecosystems are undermined by ongoing population decay due to intensified anthropogenic activities. Given the limited resources available to invest in conservation programs and the increasing numbers of threatened species due to fast-paced rate of biodiversity loss, recent efforts have been made into identifying species and areas of high conservation priority for protecting their ecological functionality. While species diversity has often been considered in guiding conservation actions, such recent interest in preserving species’ ecological contributions has advocated for integrating functional diversity in conservation planning. In this study, I assessed the global patterns of the functional and taxonomic diversity (i.e. functional richness and species richness, respectively) of marine megafauna to identify areas of exceptional functional importance. Accordingly, I identified the degree of congruence between locations of high species and functional richness by means of hotspots overlap analysis and applied a novel conservation index, FUSE (Functionally Unique, Specialized, and Endangered) to identify areas of conservation prioritization according to species’ contributions to functional diversity and their endangerment status. Hotspots of functional richness overlapped only marginally with those of species richness (by 34.5%). The South-West Pacific resulted as a major hotspot of exceptionally high functional richness, while the Caspian Sea and Gulf of Mexico were identified as areas of potential conservation priority harbouring species with high-ranking FUSE scores. Furthermore, the South-West Pacific was also an aggregation centre of high-ranking FUSE species. Overall, this study showed that setting conservation priority areas based on metrics of species diversity alone would be insufficient for safeguarding the ecological contributions of marine megafauna to the ecosystem, and that larger protection areas should be considered.